On Guido Liguori’ On Guido Liguori’s Gramsci’s Pathways - Chino , Takahiro (International Gramsci Journal, 2023)
This is a review by Takahiro Chino of Guido Liguori’s Gramsci’s Pathways, Chicago, Haymarket Books, 2015.